2020
DOI: 10.12968/jowc.2020.29.12.692
|View full text |Cite
|
Sign up to set email alerts
|

AI technology for remote clinical assessment and monitoring

Abstract: Objective: To report the clinical validation of an innovative, artificial intelligence (AI)-powered, portable and non-invasive medical device called Wound Viewer. The AI medical device uses dedicated sensors and AI algorithms to remotely collect objective and precise clinical data, including three-dimensional (3D) wound measurements, tissue composition and wound classification through the internationally recognised Wound Bed Preparation (WBP) protocol; this data can then be shared through a secure General Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…In fact, 14 of the excluded studies focused on the classification of body postures or movements (e.g., [19][20][21][22][23][24][25][26]), which represents a very important subject in the monitoring of PU. Four of the excluded studies (e.g., [27][28][29][30]) addressed wound image analysis to characterize or classify PU. Despite describing interesting works, these studies did not propose any type of actions or consequences related to the postures and movements identified, or the stage (i.e., pressure ulcers classification according to the level of tissue damage), to improve the prevention and treatment of PU.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…In fact, 14 of the excluded studies focused on the classification of body postures or movements (e.g., [19][20][21][22][23][24][25][26]), which represents a very important subject in the monitoring of PU. Four of the excluded studies (e.g., [27][28][29][30]) addressed wound image analysis to characterize or classify PU. Despite describing interesting works, these studies did not propose any type of actions or consequences related to the postures and movements identified, or the stage (i.e., pressure ulcers classification according to the level of tissue damage), to improve the prevention and treatment of PU.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…In technical terms, a CNN is a type of neural network that employs ML algorithms to process various types of data and draw conclusions and has been shown to achieve high accuracy in recognizing objects [8]. A CNN consists of multiple convolutional layers, the main building blocks to which filters are applied, each responsible for combining model inputs (e.g., images and sensor data) to create a map from which to extract relevant features or components/relationships of the model inputs.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…This study uses deep-ML approaches to distinguish connections or predictive measures between these two data types. This combination has the potential to provide objective data through continuous remote monitoring of the wound, similar to the protocol by Zoppo and colleagues using remote monitoring through a telehealth platform [8] to alert patients about wound complications and to communicate critical information to clinicians. The long-term objective is to improve subjective wound assessment by providing a more "precise" parameter for healing status.…”
Section: Objectivementioning
confidence: 99%
“…In order to evaluate the precision and the usefulness of the device in the remote wound evaluation, a clinical trial has been conducted among 150 patients. The results showed that AI would really help the clinician to conduct an effective remote wound assessment, reaching 97% of accuracy in the WBP classification and tissue segmentation analysis compared with that performed by clinicians 67 …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that AI would really help the clinician to conduct an effective remote wound assessment, reaching 97% of accuracy in the WBP classification and tissue segmentation analysis compared with that performed by clinicians. 67 …”
Section: Introductionmentioning
confidence: 99%